Differences in bioactivity of three endemic Nepeta species arising from main terpenoid and phenolic constituents - Nestorović Živković, Jasmina Milan; Živković, Suzana; Šiler, Branislav; Aničić, Neda; Dmitrović, Slavica; Divac Rankov, Aleksandra; Giba, Zlatko; Mišić, Danijela (Archives of Biological Sciences, 2018)
Methanol extracts of three endemic Nepeta species were analyzed for their main secondary metabolites, terpenes and phenolics, and further investigated for antioxidant capacity and embryonic toxicity in zebrafish. UHPLC/DAD/(±)HESI-MS/MS analysis showed that the dominant compound in N. rtanjensis was trans,cis-nepetalactone, the cis,trans isomer of this monoterpene lactone was dominant in N. sibirica, while nepetalactone was detected only in traces in N. nervosa. In all investigated species, rosmarinic acid was the dominant phenolic compound, while other identified phenolic acids (chlorogenic, neochlorogenic and caffeic) were present in considerably lower amounts. ABTS and DPPH assays showed that the methanol extracts of N. rtanjensis, N. sibirica and especially N. nervosa possessed strong antioxidant activities, with the FRAP assay revealing high ferric-reducing abilities for all three tested species. Such a strong antioxidant potential, especially as manifested in the DPPH and FRAP assays, can be attributed to phenolic acids, and in the first place to rosmarinic acid. Increased lethality of zebrafish embryos in any of the treatments was not observed, but several toxic effects on embryonic development were recorded, such as pericardial and yolk sac edema. As in other Nepeta species, the three studied endemic species possessed a great potential for food conservation or as medicinal supplements if applied in optimized concentrations; however, alternative sources of plant material (e.g. field cultivation) should be established bearing in mind their vulnerability in nature. https://doi.org/10.2298/ABS170616026N Received: June 16, 2017; Revised: July 20, 2017; Accepted: July 20, 2017; Published online: July 26, 2017 How to cite this article: Nestorović-Živković J, Živković S, Šiler B, Aničić N, Dmitrović S, Divac-Rankov A, Giba Z, Mišić D. Differences in bioactivity of three endemic Nepeta species arising from main terpenoid and phenolic constituents. Arch Biol Sci. 2018;70(1):63-76.